Preparation of Financial Statements for a Trading Company for Students at SMAN 2, Jakarta, Indonesia - Nastasya Cindy Hidajat (Advances in Community Services Research, 2026)
Purpose: The limited scope of accounting education, which tends to be theoretical, means that high school students lack sufficient experience in preparing financial statements for merchandising companies. This PKM activity aims to improve students’ understanding of basic accounting concepts, the preparation of financial statements for merchandising companies, and financial literacy. Method: The activity was held at SMAN 2 Jakarta on May 29, 2026, lasted 120 minutes, and involved 28 eleventh-grade students. The methods used included interactive lectures, participatory training, case studies, discussions, mentoring, practice evaluations, and feedback questionnaires. Results and Discussion: Prior to the intervention, students struggled to understand how to prepare financial statements in a practical context. The training successfully improved students’ understanding of basic accounting concepts and the characteristics of trading companies, as well as their ability to prepare simple financial statements. The participants’ enthusiasm and active engagement during the activity demonstrated that the training methods were well-suited to the partners’ needs. Implications: This initiative helps improve students’ financial literacy and basic accounting skills and has the potential to be further developed through ongoing mentoring programs.